A forensic investigation on the persistence of organic gunshot residues. (November 2018) - Maitre, Matthieu; Horder, Mark; Kirkbride, K. Paul; Gassner, Anne-Laure; Weyermann, Céline; Roux, Claude; Beavis, Alison
Abstract: Gunshot residues (GSR) are a potential form of forensic traces in firearm-related events. In most forensic laboratories, GSR analyses focus on the detection and characterisation of the inorganic components (IGSR), which are mainly particles containing mixtures of lead, barium and antimony originating from the primer. The increasing prevalence of heavy metal-free ammunition challenges the current protocols used for IGSR analysis. To provide complementary information to IGSR particles, the current study concentrated on the organic components (OGSR) arising from the combustion of the propellant. The study focused on four compounds well-known as being part of OGSR: ethylcentralite (EC), methylcentralite (MC), diphenylamine (DPA), N -nitrosodiphenylamine ( N -nDPA). This study assessed the retention of these OGSR traces on a shooter's hands. The overall project aim was to provide appropriate information regarding OGSR persistence, which can be suitable to be integrated into the interpretation framework of OGSR as recommended by the recent ENFSI Guideline for Evaluative Reporting in Forensic Science. The persistence was studied through several intervals ranging from immediately after discharge to four hours and two ammunition calibres were chosen: .40 S&W calibre, used by the NSW Police Force; and .357 Magnum, which is frequently encountered in Australian casework. This study successfully detected the compounds of interest up to four hours after discharge. The trends displayed a large decrease in the amount detected during the first hour. A large variability was also observed due to numerous factors involved in the production, deposition and collection of OGSR.